Influence of reverted austenite on the texture and magnetic properties of 350 maraging steel - Abreu, Hamilton Ferreira Gomes de (2015)
The aging temperature to improve magnetic properties in Maraging-350 steel (Mar-350) is limited by the onset of austenite reversion. The traditional process of cooling after aging is to remove the piece from the oven and then to air cool it. The purpose of this research was to characterize the reverted austenite and to investigate the effect of cooling below the martensite start temperature (Ms) on the magnetic properties. The Mar350 samples aged at temperatures above 550 °C, and subsequently cooled in liquid nitrogen presented less austenite than samples cooled in air, resulting in higher magnetization saturation and a lower coercive force. A combination of optical microscopy (OM), X-ray diffraction (XRD) and electron backscatter diffraction (EBSD) techniques were used to characterize the presence of reverted austenite. The crystallographic texture of both martensite and reverted austenite were analyzed. The texture of the reverted austenite coincides with the texture of the parent austenite indicating that a phenomenon of texture memory is present.